Environmental temperature and pathogen dose affect histologic lesion count and severity in Notophthalmus viridescens infected with Batrachochytrium salamandrivorans - Sheley, Wesley C.; Wilber, Mark Q.; Carter, Edward Davis; Gray, Matthew J.; Miller, Debra L. (Frontiers in Amphibian and Reptile Science, 2025)
IntroductionBatrachochytrium salamandrivorans (Bsal) was discovered a decade ago in Europe, where it is emerging and decimating salamander populations. North America, a global hotspot for salamander biodiversity, faces risk of Bsal introduction through trade or other pathways. An abundant salamander species in these systems, the eastern newt Notophthalmus viridescens, is highly susceptible to Bsal and may play an important role in Bsal epidemiology if the pathogen is introduced. However, we know very little about the physiological mechanisms contributing to the pathogenesis of Bsal chytridiomycosis. This limits our ability to treat infection on an individual level and predict the evolutionary responses of resistance and tolerance on the population level following Bsal invasion.MethodsWe tested the hypothesis that morbidity and mortality of Bsal-infected individuals are directly related to skin lesions, after controlling for Bsal infection intensity. To test this, we compared Bsal-induced lesions in eastern newts among four Bsal zoospore doses (5x103–6 per 10 mL) and maintained at three environmental temperatures (6, 14, and 22°C). Following euthanasia, animals were processed for histologic examination and Bsal-associated lesions were counted and graded for severity on a scale of 1–5. Additionally, dermal glands were examined for Bsal invasion and all internal organs were assessed.ResultsNewts exposed at 22°C did not become infected by Bsal. Newts exposed at 14°C had more lesions compared to those exposed at 6°C across all zoospore doses. For the lowest three zoospore exposure doses, as zoospore dose increased, so did lesion count. Additionally, there was a strong negative relationship between lesion count and survival, after accounting for Bsal infection intensity, suggesting that lesions are contributing to Bsal pathogenesis beyond infection intensity. Lesions were most abundant in the hindlimbs, cloacal region, and tail. There were no Bsal-related abnormalities in internal organs; further supporting our hypothesis that morbidity and mortality in infected individuals are directly related to skin lesions.DiscussionThis is the first Bsal susceptibility study which has evaluated the number, distribution, and severity of histologic lesions in Bsal-infected hosts across multiple temperatures. These results provide insight into the pathogenesis of Bsal chytridiomycosis, and how environmental temperature can impact disease progression. Additionally, these results indicate swabbing the hindlimbs, cloacal region, and tail might increase detection of Bsal on infected animals due to locally increased lesion prevalence.